Chemotherapy-related adverse drug reaction and associated factors among adult cancer patient attending Jimma medical center oncology unit, Southwest Ethiopia - Mukerem Sultan Shrmeka; Mubarik Fetu Semman; Biruk Tafese Moges; Feki Nekir Dereja; Aster Wakjira Garedo (PLoS ONE, 2025)
Background In 2017, reports of adverse drug reactions worldwide reached an estimated 35 million.Chemotherapeutic agents were one of the most often implicated pharmacological classes in inducing adverse drug reactions. Adverse drug reactions increase the overall expense and mortality. Adverse drug reactions increase morbidity, mortality, hospitalization rate and financial expenses. Therefore, this study intended to assess chemotherapy-related adverse drug reactions and associated factors among adult cancer patients. Patients and method A facility-based prospective observational study was conducted from July 2022 to October 2022 at Jimma Medical Center’s oncology unit. A standard data collection tool (Naranjo’s algorithm, modified Hartwig’s severity scale, and modified Schumock-Thornton criteria) was used for assessment of causality, severity, and preventability of adverse reactions, respectively. Socio-demographic profile and any adverse drug reactions reported were collected separately. The data was collected by one pharmacist and two nurses after giving training. Data was entered into Epidata version 4.6.0 and analyzed by SPSS version 25. Bivariate and multivariable logistic regression was conducted to identify independent predictors of the pattern of adverse drug reaction occurrence. A P-value of 0.05 was taken as statistically significant. Result Out of 154 patients enrolled in the study, 66.2% were female. The mean age of patients was 41.20 ± 13.54 years. From the total, 98 (63.6%) cases developed a total of 198 adverse drug reactions. Out of them, 59.2% were female. The most commonly encountered adverse drug reactions were nausea and vomiting (33.8%) and hair loss (29.3%). Most of the reactions were probable (61.1%) in causality, mild (66.2%) in severity, and not preventable (43.9%) in nature. Female sex (AOR = 1.054; 95% CI= (1.021–1.087); P = 0.001), number of chemotherapy treatments (AOR = 3.33; 95% CI= (1.301–8.52); P = 0.012), and elderly age (AOR = 3.065; 95% CI= (1.01–9.296); P = 0.048) were associated with occurrences of adverse drug reactions. Conclusion We can deduce from the data that adverse drug reactions are a significant concern for patients undergoing chemotherapy, with nearly two-thirds experiencing ADRs. The most common reactions are nausea and vomiting, which are mostly mild and probable. Age, gender, and the use of several chemotherapy drugs were associated with an increased risk of adverse drug reactions. Hence all concerned bodies should make an effort for early detection and take preventive measure of chemotherapy-related adverse drug reactions. Where feasible, use chemotherapy protocols with alower risk of ADRs. Evaluate dose adjustments for elderly patients. Implement protocols for risk assessment before initiating chemotherapy.